VARIETAL DIVERSITY IN THE CULTIVATION OF RUBUS IDAEUS L. - Rozhko І. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
The International Raspberry Organization (IRO) unites 13 countries, which together account for about 80 % of the world’s raspberry production. The IRO includes the following countries: Australia, Bulgaria, Canada, Chile, China, England, France, Hungary, Mexico, Poland, Serbia, Scotland, and the United States of America. Since 2022, Ukraine has been represented in the IRO by Iryna Kukhtina, President of the Ukrainian Berry Association and Head of the Union of Innovative Farming and Cooperation. Geographical differences among the countries that commercially cultivate Rubus idaeus L. influence the selection of varieties, which vary in their environmental requirements, ripening and harvesting periods (in temperate regions, raspberries are harvested in early summer, while in equatorial regions, they can be grown year-round), and cultivation technologies. The success of global Rubus idaeus L. production is driven by an integrated approach that combines breeding efforts (focused on developing and introducing varieties with desirable traits such as cold resistance, drought tolerance, pest resistance, adaptability to diverse cultivation and processing technologies, and alignment with consumer preferences) with optimized production methods that account for climatic variability in yields. The varietal diversity of Rubus idaeus L. is a key factor in stabilizing production, enhancing economic efficiency, and ensuring the competitiveness of the modern berry industry in the global market. Genetic, morphological, and physiological differentiation among varieties provides wide adaptive plasticity, which is critical in the context of variable environmental conditions, including rapid climate change. This diversity contributes to higher yields, stable fruiting under stress conditions, and improved fruit quality for consumers.